Writing Self, Writing Empire: Chandar Bhan Brahman and the Cultural World of the Indo-Persian State Secretary By Rajeev Kinra (Oakland: University of California Press, 2015. 371 pages.) (American Journal of Islam and Society, 2016)
The seventeenth century marks an exciting period in the life of Persian literarycultures in northern India. Established as a language of administration byTurco-Afghans in the early thirteenth century, several centuries later Persianhad extended well beyond its initial administrative strongholds to become animportant medium for literary and religious composition, historiography, andtranslation. In a literary environment that prized both literary aesthetics andfierce rivalries, the massive textual production on vastly diverse subjects, aswell as the presence of literary salons, standalone bookstalls, and mushā‘irahs(poetic assemblies), cumulatively point to a lively Persian literary culture thatechoed across political, religious, and socio-cultural terrains.Unfortunately, most of the scholarship on Persian in the medieval Indiancontext over the past decades has failed to illuminate this dynamic scene.Moreover, most studies seek to highlight Persian’s influence on India or examineIndia’s civilizational impact on Persian. Both paradigms assume a natural(read: Iranian) ecumene for Persian and thus do not critically considerthe slippage between linguistic, ethnic, and geographic designations wh